Implementasi Manajemen Pembiasaan Sholat Dhuha Dalam Pembentukan Karakter Disiplin Siswa Di Sma Islam Al-Amalul Khair Palembang - Alda Olyvia; Ade Akhmad Saputra (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study aims to analyze the implementation of Dhuha prayer habits in fostering disciplined character among students at Al-Amalul Khair Islamic High School in Palembang. The study employs a qualitative descriptive approach using the case study method. Data collection techniques included observation, interviews, and documentation. The results of the study indicate that the habit of performing Dhuha prayer, when carried out routinely, in a structured manner, and consistently, is effective in fostering students’ disciplined character, such as punctuality, responsibility, and adherence to school rules. The success of the program is influenced by effective management through the planning, implementation, and evaluation stages, as well as the support of teachers who serve as role models in religious activities. In addition to fostering discipline, the Dhuha prayer program also has a positive impact on students’ spiritual aspects, such as increased awareness of worship, inner peace, and the development of positive habits in daily life. However, during implementation, some students still lack discipline, necessitating more intensive supervision and guidance. Thus, the implementation of Dhuha prayer habit-forming management can serve as an effective strategy for fostering disciplined character among students in an Islamic school environment.